The Prevalence of Commonly Encountered Parasites in Sheep in Iğdır Province, Turkey - Fatma Ertaş; Ayşe Sona Karakuş; Adnan Ayan (Turkish Journal of Agriculture: Food Science and Technology, 2022)
Sheep farming is an important segment of the livestock sector in Turkey. However, low meat, milk, leather and wool production due to various parasitic diseases has adversely affected this sector. This study was carried out by using stool and tissue samples collected from 300 sheep registered with the Provincial Directorate of Agriculture and Forestry in Iğdır, Turkey. Stool samples were collected using native, flotation and sedimentation methods to diagnose common parasites. In addition, parasitic diagnoses were strengthened with the migration paths of parasites and the presence of cysts as a result of macroscopic examination of the liver and lungs of sheep slaughtered in the slaughterhouse. From the data obtained, the prevalence and material damage and loss of workforce of parasites were determined using appropriate statistical programs. Fascioliasis 16.7%, Nematodirosis 20% Echinococcosis 29% Dicrocoeliasis 32% varied. It was concluded that the parasite population is high in sheep in Iğdır province, Turkey. Accordingly, attention was drawn to the issue of necessary protection and controls.